On the Nisan-Ronen conjecture - Christodoulou, G; Koutsoupias, E; Kovacs, A (Association for Computing Machinery, 2022)
The Nisan-Ronen conjecture states that no truthful mechanism for makespan-minimization when allocating m tasks to n unrelated machines can have approximation ratio less than n. Over more than two decades since its formulation, little progress has been made in resolving it and the best known lower bound was a small constant. This note gives an overview of our recent paper that gives a lower bound of 1 + √n − 1.